Association between the dietary index of gut microbiota and abnormal bowel symptoms in U.S. adults: a cross-sectional study based on NHANES 2007–2010 - Sicheng Shen; Huayi Feng; Chuyue Wang; Yingqi Yang; Zhiyang Chen; Xiaopeng Wang; Jiacheng Li (BMC Gastroenterology)
Abstract Background The Dietary Index of Gut Microbiota (DI-GM) is a newly developed measure for assessing diet quality in relation to the diversity of the gut microbiome. However, whether it is associated with the risk of chronic constipation and chronic diarrhea remains unclear. Methods We analyzed data from 7,943 U.S. adults aged 20 years and older who participated in the 2007–2010 National Health and Nutrition Examination Survey (NHANES). Weighted logistic regression, subgroup analysis, and restricted cubic spline (RCS) models were used to assess the association between the DI-GM and abnormal bowel symptoms. Results A higher DI-GM score was significantly associated with a reduced risk of abnormal bowel symptoms. For each 1-point increase in the DI-GM, the risk of constipation decreased by 12.4% (OR = 0.876, 95% CI = 0.806–0.951, p = 0.002), and the risk of diarrhea decreased by 14.1% (OR = 0.859, 95% CI = 0.789–0.936, p < 0.001). Compared with the lowest DI-GM quartile, the highest quartile showed a markedly lower risk of both constipation (OR = 0.487, 95% CI = 0.340–0.696, p < 0.001) and diarrhea (OR = 0.480, 95% CI = 0.338–0.682, p < 0.001). RCS analysis indicated a significant linear association between the DI-GM and the risks of both constipation (nonlinear p = 0.686) and diarrhea (nonlinear p = 0.136). Conclusions The DI-GM was negatively associated with the prevalence of abnormal bowel symptoms. Further longitudinal studies are warranted to confirm these findings and to inform dietary strategies for gut health.